Integration of Hadith-Based Moral Education in Holistic Education in the 5.0 Era: A Systematic Literature Review - Primarni, Amie; Fa’atin, Salmah; Makmudi, Makmudi; Nuhdi, Asep; Herlina, Herlina (Journal of Education and Computer Applications, 2025)
This study explores the integration of hadith-based moral education within the framework of 5.0 holistic education through a Systematic Literature Review (SLR). The purpose is to identify the principles, values, and strategies found in prophetic traditions that support the moral development of children, and to examine their alignment with holistic educational paradigms. The method involves collecting relevant literature from databases such as Google Scholar, Scopus, Web of Science, and DOAJ using specific keywords. Articles were screened using the PRISMA flowchart and analyzed thematically to extract recurring concepts and educational practices. The findings indicate that hadith-based moral education emphasizes emotional intelligence, spiritual growth, and value-based learning—core aspects of holistic education. However, research explicitly connecting hadith and holistic approaches remains scarce. The limited incorporation of prophetic values in current educational systems reflects a significant gap and highlights the need for contextual adaptation. This study’s originality lies in its attempt to bridge Islamic traditions with modern educational needs through an integrative framework. Limitations include the scope of databases and possible language bias. In conclusion, this study offers both theoretical insights and practical guidance for educators, parents, and policymakers seeking to foster character development through spiritually grounded, holistic learning models.